Mendeley: Sitasi Dalam Penulisan Artikel Ilmiah Pada Jurnal Bereputasi - Nico Harared; Muhammad Rinzat Iriyansah (Universitas Muhammadiyah Surabaya, 2021)
Tujuan dari kegiatan pengabdian kepada masyarakat ini adalah untuk memberi pemahaman mengenai penggunaan mendeley dalam artikel ilmiah pada dosen fakultas teknik ITBU. Dengan pengenalan ini para dosen diharapkan dapat memberi pemahaman mengenai penggunaan aplikasi mendeley dalam artikel ilmiah secara komprehensif dan terlibat aktif dalam penulisan penelitian dengan sesama rekan dosen, mahasiswa dan semua pihak yang terkait. Metode pelaksanaan kegiatan ini dibagi ke dalam tiga langkah pelaksanaan kegiatan (workshop): (1) practical guidelines and tips on how to write at national accredited journal,(2) introducing mendeley, and (3) practice of mendeley ini diharapkan dapat menambah pengalaman belajar yang baru bagi para dosen. Hasil kegiatan pengabdian kepada masyarakat ini mayoritas para dosen dapat informasi dan pengetahuan baru mengenai aplikasi pengutipan dan sitasi mendeley ini. Dampak positif dirasakan oleh para dosen dari kegiatan pelatihan yang diselenggarakan dengan tujuan memudahkan penulisan pengutipan dan sitasi pada artikel ilmiah. Antusiasme yang positif dan rasa ingin tahu para dosen ditunjukkan secara interaktif selama kegiatan pelaksanaan. Kegiatan pengabdian kepada masyarakat ini berjalan dengan lancar sesuai dengan harapan serta terjalin komunikasi yang baik antara pihak mitra dengan tim pelaksana.Kata Kunci: jurnal bereputasi, mendeley, karya ilmiah Mendeley: Citation in Writing Scientific Articles in Reputable JournalsABSTRACTCurrently, some lecturers have not been able to make citations automatically using the application. This can be seen from several articles published in journals. One application that makes it easier to write citations internationally is Mendeley. The purpose of this community service activity is to provide an understanding of the use of Mendeley in scientific articles for ITBU engineering faculty lecturers. With this introduction, lecturers are expected to provide an understanding of the use of the Mendeley application in scientific articles in a comprehensive manner and to be actively involved in research writing with fellow lecturers, students and all related parties. The method of implementing this activity is divided into three steps of implementing activities (workshops): (1) practical guidelines and tips on how to write at a national accredited journal, (2) introducing mendeley, and (3) practice of mendeley is expected to add to the learning experience new to the lecturers. The results of this community service activity are the majority of lecturers get new information and knowledge about this Mendeley citation and citation application. The positive impact was felt by the lecturers from the training activities held with the aim of facilitating the writing of citations and citations in scientific articles. The positive enthusiasm and curiosity of the lecturers were shown interactively during the implementation activities. The abdimas activities run smoothly as expected and good communication is established between the partners and the abdimas team.Keywords: reputable journal, Mendeley, scientific work